(untitled) (Latakia University Journal -Basic Sciences Series, 2025)
This work focuses on the manufacturing of a simple and rapid selective electrode for determining the organophosphorus pesticide dimethoate, using copper oxide as an electrochemically active material. The copper oxide is mixed with graphite powder and paraffin oil as a plasticizer to achieve the appropriate pasty consistency. A potential study of the mixing ratios between graphite powder, active material, and plasticizer was conducted to determine the optimal ratio. The electrode exhibits a Nernst response within a concentration range of (1×10^-4 to 1×10^-6) mol/L, yielding a Nernst slope of 30.2 ± 2 mV/decade. The effects of the pH value of the medium on the Nernst response of the fabricated electrode as well as the response time were studied, and temperature effects, were studied. The results showed stability of the potential at pH = 4 and a response time ranging from 33 to 60 seconds at temperatures between 20 and 35 °C. The potential selectivity coefficients of the proposed electrode were calculated using the Matched Potential Method (MPM). The results indicated that the proposed electrode demonstrates high selectivity for dimethoate in the presence of various interfering ions. The concentration of dimethoate in some commercial samples was determined using the proposed electrode, yielding recoveries of 102.006% and 104.779%. The results were compared with a reference method, and the Fisher test indicated good agreement between the results of two methods. Therefore, this selective electrode can be adopted as a potential method for the determination of dimethoate pesticide.